Riverbank erosion displacement as constraint to rural development : a sociological study in Bangladesh - Hamide, Md. Shamim (Kulliyyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2018)
The environmental disaster of riverbank erosion displacement exercises a devastating impact upon the livelihood of most of rural population in riverine Bangladesh. It displaces millions of riparian people from their original homestead and consequently they are rendered as landless, homeless, and unemployed. This thesis contributes to the broad ranging topic of coping with natural disaster from a sociological perspective. Utilizing a general systems theory framework. The thesis is devoted to depicting the familial survival strategies of the affected people in Telikhali region in Southwestern coast of Bangladesh, who generally formulate and undertake those strategies in their own ways in the devoid of organizational support. The research employs multiple qualitative techniques and is primarily based on the data gathered through direct interviewing with purposively chosen of 163 displacees in Telikhali region. The research employed observation method, case studies, focus group discussions (FGDs) and also based on informal interviews with various stakeholders. The empirical primary data gathered through these methods and techniques are appropriately used to analyse the units of this research. The secondary information from other research documents is also used in this research for arguing with and/or refuting the findings. This research enthusiastically tries to find out the prodigious need induced by riverbank erosion displacement impelling the displacee people in crafting survival strategies, cope with changes in socio-economic hierarchy and modify occupational and economic activities. The struggles of the riverbank erosion induced migrants are multi-fold: mostly tied to the break-up of the familial and social ties and land ownership patterns. On rural development front, it is found that government and non-government agencies play a nearly insignificant role in repairing the damages caused by riverbank erosion. In this way, the engagement of Telihali's displacee population in formulation of their survival strategies in both farm and nonfarm level, and in household chores destroy their total socialization and proper rural development. Based on the findings, a number of suggestive policy measures that the planners and implementers may consider for the future development of rural infrastructure in riverbank erosion and other disaster prone rural areas of Bangladesh are embedded in the end of the thesis.